1996
DOI: 10.1177/089686089601600608
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Recombinant Human Erythropoietin Administered Subcutaneously to Capd Patients Once Weekly

Abstract: Objective The purpose of the present study was to compare the dosage requirements of recombinant human erythropoietin (rHuEPO) administered subcutaneously (SC) either one or three times weekly. Design A randomized, prospective study. .Setting: The patients were recruited from two university hospitals and five county hospitals. Patients Thirty-three anemic patients on continuous ambulatory peritoneal dialysis (CAPD) treatment for endstage renal failure completed the study. Interventions Initially, all were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
1
9
1
1
Order By: Relevance
“…The agreement of the three data sets indicates the robustness of the results and provides a convincing demonstration of equivalence between once-weekly and three times weekly epoetin b administration frequencies. Furthermore, these data confirm the results of previous studies suggesting the effectiveness of once-weekly epoetin treatment [10][11][12][13][14][15].…”
Section: Statistical Considerationssupporting
confidence: 90%
See 1 more Smart Citation
“…The agreement of the three data sets indicates the robustness of the results and provides a convincing demonstration of equivalence between once-weekly and three times weekly epoetin b administration frequencies. Furthermore, these data confirm the results of previous studies suggesting the effectiveness of once-weekly epoetin treatment [10][11][12][13][14][15].…”
Section: Statistical Considerationssupporting
confidence: 90%
“…Epoetin administration frequency has attracted a high level of attention in recent years, and numerous small-scale studies have shown comparable efficacy and tolerability of once-weekly vs more frequent administration [10][11][12][13][14]. The results of two large-scale, randomized, controlled trials of once-weekly administration of epoetin b became available recently [15,16].…”
Section: Once-weekly Administration Of Epoetinmentioning
confidence: 99%
“…Several studies showed that a low Kt/V index indicates anemia, which necessitates higher EPO dose to maintain target plasma hemoglobin levels (18,19). However, some studies found no association between them (12). Our data showed no significant relationship between these variables, as well.…”
Section: Discussioncontrasting
confidence: 62%
“…This leads to lower percentage of anemia in patients on PD in comparison with HD (11). In addition, treatment response to anemia is better in patients treated with PD compared to patients with HD (12). The production of EPO by peritoneal macrophages (6) and losing a little blood during dialysis procedure then in HD are some interacted factors.…”
Section: Introductionmentioning
confidence: 99%
“…Frifelt et al 11 prospectively compared the maintenance dosage requirement of a once weekly SC regimen with a thrice weekly regimen in anaemic patients on continuous ambulatory peritoneal dialysis. All patients were treated with SC EPO three times a week until the haemoglobin stabilized at 10–12 gm/dL for 3 months before being randomized into the study.…”
Section: Discussionmentioning
confidence: 99%